Low bone mineral density for age/osteoporosis in triple A syndrome—an overlooked symptom of unexplained etiology. Issue 2 (February 2016) - Dumic, M.; Putarek, N.; Kusec, V.; Barisic, N.; Koehler, K.; Huebner, A.
Abstract Summary Triple A syndrome (alacrima, achalasia, adrenal failure, progressive neurodegenerative disease) is caused by mutations in theAAAS gene which encodes the protein alacrima achalasia adrenal insufficiency neurologic disorder (ALADIN). Our investigation suggests that low bone mineral density (BMD) for age/osteoporosis could be a common but overlooked symptom of unexplained etiology in this rare multisystemic disease. Introduction The purpose of this study is to evaluate incidence and etiology of BMD for age/osteoporosis, a possibly overlooked symptom in triple A syndrome. Methods Dual-energy X-ray absorptiometry (DXA) of the femoral neck, total hip, lumbar spine, and radius, bone turnover markers, minerals, total alkaline phosphatase (ALP), 25-hydroxy vitamin D (25-OHD), 1, 25-dihydroxy vitamin D (1, 25-OH2D), intact parathyroid hormone (PTH), and adrenal androgens (dehydroepiandrosterone sulfate (DHEAS) and androstenedione) were measured in five male and four female patients. Results At time of diagnosis, low BMD for age was suspected on X-ray in seven of nine patients aged 2–11 years (not performed in two patients); normal levels of minerals and ALP were found in nine patients and low levels of adrenal androgens in eight patients (not measured in one patient). Reevaluation 5–35 years after introduction of 12 mg/m2 /day hydrocortisone showed low BMD for age in two children, osteopenia in one, and osteoporosis in six adults. Normal levels of minerals, ALP, PTH, 1, 25-OH2D, procollagen type 1, crosslaps, and osteocalcin were found in all patients. Low levels of adrenal androgens were found in all and 25OHD deficiency in six patients. Body mass index was <25 % for age and sex in eight of nine patients. Conclusion Low BMD for age/osteoporosis in our patients probably is not a result of glucocorticoid therapy but could be the consequence of low level of adrenal androgens, neurological impairment causing physical inactivity, inadequate sun exposure, and protein malnutrition secondary to achalasia. Considering ubiquitous ALADIN expression, low BMD/osteoporosis may be a primary phenotypic feature of the disease. Besides optimizing glucocorticoid dose, physical activity, adequate sun exposure, appropriate nutrition, and vitamin D supplementation, therapy with DHEA should be considered.